Strategi Pengembangan SDM pada Pasar Seni " Pasar Besar" di Kuala Lumpur - Suparjo; Kumala, Charisha Mahda; Dana, Yoga Adhi; Sunarsih, Endang Sri (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Pasar Seni, also known as Central Market or Pasar Besar, is now one of the main tourist destinations in Kuala Lumpur and has made a significant contribution to Malaysia's creative economy sector. widely used as a reference in various countries. The purpose of this study was to determine the strategy for developing human resources. Data came from 38 traders and 2 managers of Pasar Seni. The research method used a qualitative approach with an exploratory case study design to understand the dynamics of Human Resource Development. The results of the study showed two main programs implemented: 1) a dynamic and integrated Training and Education Program, and 2) a Lifelong Learning Approach. The implementation of the learning approach faced several significant challenges, namely skepticism about the benefits of learning, low digital literacy among senior artists Based on the analysis of current conditions, the community service team proposed a comprehensive and integrative sustainable human resource development model "ARISE Model" as a framework for sustainable human resource development